Lung Sonography in Obstetrics during COVID-19 - Recker, Florian; Weber, Eva; Strizek, Brigitte; Gembruch, Ulrich; Seibel, Armin (Geburtshilfe und Frauenheilkunde, 2020)
In the current coronavirus SARS-CoV-2 pandemic, certain patients are becoming seriously ill. Lung pathologies are common, and some patients even go on to develop acute respiratory distress syndrome (ARDS), which requires intubation and artificial respiration of the critically ill patient. Imaging of the lung is absolutely necessary to obtain a diagnosis, assess the course of disease and for treatment. Particularly in gynecology and obstetrics (OBGYN), ultrasound scans of the lung can be a useful additional tool when caring for pregnant patients in the delivery room. As obstetricians use ultrasound imaging a lot in routine clinical practice, in the current pandemic setting, routine prenatal imaging screening could be expanded by the addition of ultrasound scans of the lung. Lung sonography can offer important additional information, particularly in obstetrics where the indications for radiation-emitting imaging are particularly restrictive. If there is a sonographic suspicion of lung involvement, then, depending on the symptoms and the morphological extent of the ultrasound findings, it may be necessary to consider admitting the patient to hospital for close fetal and maternal monitoring.In der gegenwärtigen Pandemiesituation des Coronavirus SARS-CoV-2 stellen sich einige Patienten als kritisch krank dar. Häufig treten Lungenpathologien auf, einige Patienten entwickeln sogar ein akutes Atemnotsyndrom (ARDS), das zu einer Intubation und künstlichen Beatmung des kritisch kranken Patienten führt. Die Bildgebung der Lunge ist für die Diagnose, die Beurteilung des Krankheitsverlaufs und die Therapie absolut notwendig. Insbesondere im Bereich der Gynäkologie und Geburtshilfe (OBGYN) kann der Lungenultraschall ein ergänzendes Hilfsmittel für schwangere Patientinnen im Kreißsaal sein. Da Geburtshelfer die Ultraschallbildgebung in ihrer täglichen Routine in hohem Maße nutzen, kann der Lungenultraschall in einer Pandemiesituation die routinemäßige pränatale Bildgebung erweitern. Er kann einen wichtigen zusätzlichen Aspekt bieten, insbesondere im Bereich der Geburtshilfe, wo die Indikationen für eine strahlenemittierende Bildgebung besonders restriktiv sein sollten. Bei sonografischem Verdacht auf eine Beteiligung der Lunge sollte je nach Symptomatik und sonomorphologischem Ausmaß der Befunde eine stationäre Aufnahme mit enger fetaler und mütterlicher Überwachung erwogen werden.
Keywords: obstetrics; lung ultrasound scan; training